Numerical study of the bearing capacity of a strip footing on tow layered clay under inclined loading - Femmam, Abla; Mabrouki, Abdelhak; Mellas, Mekki (Journal of Applied Engineering Science & Technology, 2018)
The bearing capacity of a strip footing resting on a homogeneous and isotropic soil has been the subject of numerous theoretical and experimental studies. However, in practice the soil is never homogeneous. It is therefore important to introduce the effect of stratification on the bearing capacity. This paper aims to indicate the modifications that must be made to the bearing capacity of a rough strip footing resting on two layered clay subjected to inclined load. The finite-difference code Fast Lagrangian Analysis of Continua (FLAC) is used to estimate the bearing capacity factor Nc* as well as the failure envelope and the inclination factors i c , in the case of inclined loading. The study is carried out considering two layers clays of different shear strengths, where the thickness of the upper clay layer is comparable to the width of a rigid footing. The results obtained show clearly that the bearing capacity of a strip footing is generally depends on the strength ratio of the soil layers (c u1 /c u2 ) and the relative thickness of the top layer (D/B).